The effect of service marketing mix on hotel preference by consumer - Nur Rushaida, Abd Rahman (2023)
For the pass few years since Covid 19 strike world globe the hotel occupancy and demand had reduce drastically. The purchasing behaviors seem to change due the pandemic and indirectly change the consumer preferences. Therefore, this research aims to determine the relationship between service marketing mix and consumer hotel preference. This study also aims to analyze the influence of service marketing mix on consumer hotel preference in this study, the 7 pillars of the service marketing mix were used to better understand preferences in the hotel service industry: product, price, promotion, place, process, physical evidence, and people. The quantitative research method via Google form questionnaire was used as the research instrument to collect data. A total of 421 respondents were selected randomly using the convenience sampling technique. Descriptive analysis, multiple regression analysis, and correlation analysis were used to analyses the data in order to achieve the objective and conduct the research. The results of the study show a positive relationship between all the dependent variables and hotel preferences. The results indicated that the services marketing mix has a coefficient of determination of 32.6%, which indicates that the services marketing mix has an influence on the customer's hotel preference. Based on the results, we conclude that physical evidence and product effects affect hotel preference. This study helps to provide recommendations based on the findings of the research in order to enhance product quality and raise the standard of physical evidence in order to increase the hotel's influence on consumer preferences and use of its facilities. Although the impact of the other factors on the hotel's preferences is minimal, they must be maintained and enhanced to optimize its performance.